Peran Balai Harta Peninggalan Dalam Peralihan Hak Tanah Bagi Keturunan Arab Di Yogyakarta - Wahyu Hadis (Lex Renaissance, 2018)
Circular Letter of the Ministry of Domestic Affairs of the Directorate General of Agrarian Number Dpt/12/63/12/69, dated December 20, 1969, stated that the certificate of inheritence can be made by a Notary, Head of District, and also the Heritage Centre. Departing from this, this study aims to analyze and understand the role of the Heritage Center in the transfer of inheritance rights to land of Indonesian citizens of Arab descent in the Special Region of Yogyakarta and understand the legal consequences if it is known that the inheritance certificate of Arab descent was issued by the Village Government or Public Notary on the transfer of Land rights. The results of the study show that in the case of the certificate of inheritance of an Indonesian citizen of Arab descent is an absolute product and the full authority possessed by the Heritage Centre, there are two legal consequences if it is known that the certificate of inheritance of Far Eastern Indonesian citizens is made by a Notary or Village Government in Submission of Transition Inheritance rights at the National Land Agency are null and void and can be canceled if there is a transfer.